Distribution and Molecular Characterization of Antibiotic-Resistant Pseudomonas aeruginosa in Hospital Settings of Sulaymaniyah, Iraq - Ali Seenaa Muhammed; Soor Taib Ahmed Hama; Ahmed Gashin Awat; Mhdin Glena Aziz; Othman Gulabakh Ali; Faiq Sarkhel Mhamad (Polish Journal of Microbiology)
Pseudomonas aeruginosa is a significant pathogen in hospital settings, notorious for its role in hospital-acquired infections and its ability to develop resistance to multiple antibiotics. This study investigates the prevalence, distribution, and antibiotic resistance gene profiles of P. aeruginosa in seven hospitals in Sulaymaniyah City. A total of 300 samples were collected from various hospital surfaces including mops, sinks, medical equipment, beds, desks, and floors. Using bacteriological, biochemical, and molecular methods, 66 isolates were confirmed as Pseudomonas species, with 26 identified as P. aeruginosa. Antibiotic susceptibility testing revealed resistance rates of 23.3% to streptomycin, 13.6% to tobramycin, 22.7% to moxifloxacin, 21.2% to levofloxacin, and 22.7% to norfloxacin. Furthermore, the antibiotic resistance gene detection showed the presence of the blaCTX-M, blaSHV, qnrB, and blaACC-1 genes among the isolates. The study highlights a 22% contamination rate of hospital surfaces with Pseudomonas species, emphasizing the urgent need for enhanced infection control measures and targeted antimicrobial stewardship to manage and reduce the spread of multidrug-resistant P. aeruginosa.